Insights into Omicron: Genomic Characterization and Inpatient Risk Assessment at Single Tertiary Hospital in Indonesia - Turbawaty DK; Komala DR; Andriyoko B (Journal of Multidisciplinary Healthcare)
Dewi Kartika Turbawaty, Dewi Ratna Komala, Basti Andriyoko Department of Clinical Pathology, Faculty of Medicine Universitas Padjadjaran/Hasan Sadikin General Hospital, Bandung, West Java, IndonesiaCorrespondence: Dewi Kartika Turbawaty, Hasan Sadikin General Hospital, Jl. Pasteur No. 38, Bandung, West Java, Indonesia, Tel +628122150145, Email dewi.kartika@unpad.ac.idPurpose: Omicron is a variant with the highest number of mutations among all Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) viruses, making whole genome sequencing (WGS) an essential tool for public health surveillance and molecular epidemiology. It is important to note that surveillance data can provide insights into the virus evolution and disease control. This study aims to provide an overview of WGS results for the SARS-CoV-2 Omicron Variant at Hasan Sadikin General Hospital Bandung.Patients and Methods: This study was conducted using an analytical observational method. Data was collected retrospectively from medical records, SARS-CoV-2 reverse transcriptase polymerase chain reaction (RT-PCR) results, and WGS results of patients at Hasan Sadikin General Hospital Bandung from July to December 2022, who met the inclusion criteria. The lineage trends, mutation profiles, characteristics differences, and factors influencing hospitalization were also described.Results: Among 239 subjects, 50 Omicron lineages were identified, with BA.5.2 (28%) and XBB.1 (19.2%) dominating since July and October 2022, respectively. The spike gene had the highest frequency, accounting for 28.8% out of the 532 types of mutations identified. In BA.5.2 lineage, 97.01, 92.53, and 100% had L452R mutation, F486V mutation, and H69/V70 deletion, respectively. In the XBB.1 lineage, 100% had R346T and N460K mutations, with no H69/V70 deletion observed. XBB.1 lineage was associated with a 5.49 times greater risk of inpatient treatment (95% CI: 1.73– 17.38) compared to BA.5.2, while the adjusted odds ratio (aOR) for the number of vaccinations was 0.45 (95% CI: 0.29– 0.7).Conclusion: BA.5.2 and XBB.1 lineage dominated Omicron variant infections from July to December 2022, with the most mutations occurring in the spike gene. Inpatient risk was influenced by the type of lineage, with XBB.1 showing a higher risk. A greater number of vaccinations significantly reduced this risk, emphasizing the protective role of vaccination.Keywords: SARS-CoV-2, Omicron variant, whole genome sequencing